2015
DOI: 10.1371/journal.pone.0131537
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Health Score and the Risk of Cardiovascular Diseases

Abstract: In 2010 the American Heart Association proposed a definition of ideal health behaviors and health factors to measure cardiovascular health, from which Huffman et al. created the Cardiovascular Health Score (CVH score) to estimate these metrics on an individual level. We performed a prospective cohort study among employees of the Kailuan Group Corporation, who underwent a physical examination in 2006–2007 to investigate the relationship between the CVH score and the risk of cardiovascular disease (CVD). A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 25 publications
4
36
0
Order By: Relevance
“…Numerous studies have established that higher numbers of ideal LS7 metrics or higher LS7 scores are strongly associated with favorable outcomes 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14. Our results are comparable to the findings of prior studies that have shown an inverse relationship between higher LS7 scores and the incidence of non‐CVD 15, 16, 17, 18, 19.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Numerous studies have established that higher numbers of ideal LS7 metrics or higher LS7 scores are strongly associated with favorable outcomes 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14. Our results are comparable to the findings of prior studies that have shown an inverse relationship between higher LS7 scores and the incidence of non‐CVD 15, 16, 17, 18, 19.…”
Section: Discussionsupporting
confidence: 86%
“…These 7 health behaviors and factors have been termed Life's Simple 7 (LS7) metrics 4. The inverse relationship between ideal CVH and CVD incidence is well documented 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14. However, research exploring the association between ideal CVH and non‐CVDs has just begun 15, 16, 17, 18, 19…”
Section: Introductionmentioning
confidence: 99%
“…The nearly 1‐point difference in CVH score would be expected to translate into disparities in incident CVD in the future. Each 1 point greater on the 14‐point CVH scale has been associated with 18% lower risk of developing stroke or myocardial infarction in a multiracial sample 25. As previous studies have noted, if CVH trends continue without rapid improvement, prevention goals will go unmet 15, 26.…”
Section: Discussionmentioning
confidence: 90%
“…3 Several multiethnic cohorts have examined AHA CVH prevalence and associated incident CVD by race. 47 The Northern Manhattan Study (NOMAS), Atherosclerosis Risk in Communities Study (ARIC), and Reasons for Geographic and Racial Difference in Stroke cohorts found increased CVD and stroke risk associated with a lower number of ideal CVH risk factors among African American participants. 57 The relation between AHA CVH and incident CVD has not been examined in the JHS, the largest single-site, prospective epidemiologic cohort of African Americans in the U.S.…”
Section: Introductionmentioning
confidence: 99%